2002
DOI: 10.1021/es001601t
|View full text |Cite
|
Sign up to set email alerts
|

Solid−Solution Speciation and Phytoavailability of Copper and Zinc in Soils

Abstract: The soil solution speciation and solid-phase fractionation of copper (Cu) and zinc (Zn) in 11 typical uncontaminated soils of South Australia were assessed in relation to heavy metal phytoavailability. The soils were analyzed for pH (4.9-8.4), soil organic matter content (3.5 to 23.8 g of C kg(-1)), total soil solution metal concentrations, Cu8 (49-358 microg kg(-1)) and Zn8 (121-582 microg kg(-1)), and dissolved organic matter (DOM) (69-827 mg of C L(-1)). The solid-liquid partition coefficient (Kd) ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 31 publications
2
93
0
8
Order By: Relevance
“…A detailed study of the soil solution thorough chemical speciation contributes to a better understanding of the mobility and availability of nutrients or phytotoxic metals (Krishnamurtiand & Naidu, 2002), despite the variability in the methods of obtaining and the dependence on edafoclimatic conditions (Wolt, 1994). In the soil solution, most of the ions are present either as free ions or interacting with other ions or molecules, forming soluble complexes (Sposito, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study of the soil solution thorough chemical speciation contributes to a better understanding of the mobility and availability of nutrients or phytotoxic metals (Krishnamurtiand & Naidu, 2002), despite the variability in the methods of obtaining and the dependence on edafoclimatic conditions (Wolt, 1994). In the soil solution, most of the ions are present either as free ions or interacting with other ions or molecules, forming soluble complexes (Sposito, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Cornu et al reported that Cd was dominated by free Cd 2+ in soil solution. While other studies showed that the dominant Cd speciation in most soil solution was Cd-organic complex [4,6]. Schmidt [28] demonstrated that the increase in DOC induced Cu mobility, which was more pronounced at high than low pH.…”
Section: Effects Of Dom On CD Speciation In Soil Solutionmentioning
confidence: 95%
“…Following this, metal-complexes dissociate to replenish the pool of free metal ions. Nevertheless, some authors [4] observed that low molecular-weight organic acids, which comprise DOM, can be taken up by plant roots along with the metals that they have bound. Hernandez-Soriano and Jimenez-Lopez [34] described how, although the metal aqueous complexes might be less available species, they may constitute a pool of readily available metal for plant uptake, and a significant increase on Pb and Zn uptake occurred concomitantly with an enhancement of the percentage of metal-organic complex in solution.…”
Section: Influence Of Dom On Plant Growth and Uptake Of CDmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioavailability of trace metals, their biological uptake, and their eco-toxicological effects on the soil biota can be better understood in terms of their chemical speciation. The mobility and bioavailability and hence potential toxicity of metal in the soil depend on its concentration in soil solution, the nature of its association with other soluble species, and the soil's ability to release the metal from the solid phase to replenish that removed from soil solution by the plants (Krishnamurti and Naidu, 2002).…”
Section: Introductionmentioning
confidence: 99%